Alice in wonderland - Carroll, Lewis (Pearson Education Ltd, 2008)
Alice falls into a rabbit hole and enters a strange and magical world called Wonderland. She meets unusual characters like the White Rabbit, the Cheshire Cat, and the Queen of Hearts. Her adventures are full of surprises. In the end, Alice wakes up and realizes it was all a dream.